Efeito da indução de humor no desempenho em teste de inteligência fluida: estratégias cognitivas e padrões de movimentos oculares - Laurence, Paulo Guirro (2018)
Mood induction and emotional states tasks are used to verify the effect of emotions on cognitive performance. Thus, emotions modulate various cognitive abilities, such as attention, working memory and decision making. Although such skills are related to fluid intelligence, studies analyzing the effects of positive or negative valence emotions on this type of intelligence are rare. The aim of the study was to analyze the effects of mood induction with positive or negative valence on fluid intelligence performance. 161 young and adults (100 women) were divided into three groups: mood induction with negative valence, mood induction with positive valence and induction of neutral emotional valence. Initially instruments were applied to assess anxiety, depression, emotional competence, intelligence, mood and salivary cortisol. Participants then watched a video of specific emotional induction related to their experimental group and responded to the mood scale again. After that, they performed on a computer with eye movement recording equipment another intelligence test (WMT-2) composed of items created according to three types of logical reasoning. In order to verify the effect of mood induction videos, a second collection of salivary cortisol was done 30 minutes after the end of the video in a part of the sample. Results show that the 3 groups did not differ in relation to the level of anxiety, depression, emotional competence, intelligence and humor at the beginning of the procedure. However, after induction, the negative induction group had higher levels of anxiety and lower motivation. No significant differences were observed between the three groups in the percentage of items' correctness and time to perform the intelligence test. However, the reverse efficiency index, evaluated by the time of the test divided by the percentage of correct answers, was better for the positive and negative induction groups than the neutral group in one of the types of rule tokens. Analysis of the ocular movement register indicates differences between the positive induction group and the neutral group in the visual exploration pattern of the test boards. Women in the positive induction group presented more correct answers and a better efficiency index than the women in the other two groups for a logical reasoning. In addition, women in the negative induction group also had a better efficiency index than the neutral group in this type of logical reasoning. The neutral induction women group performed worse than the other two female groups in the visual exploration pattern of the test boards. Thus, the positive valence humor induction procedure influenced the efficiency in solving a type of logical reasoning, as well as in the visual exploration of the test boards. Lastly, negative correlations were found between salivary cortisol levels after the induction of mood with the mean time in WMT-2, with emotional competence and with the inverted efficiency index for one of the types of logical reasoning